Marginal oil and gas field development using stranded and flaring gas - Kartohardjono, Sutrasno; Fadilah, Hadid (Edelweiss Applied Science and Technology, 2024)
Indonesia’s abundant natural gas reserves present an opportunity to transition towards natural gas as a primary energy source due to its efficiency and industrial versatility. However, stranded gas and flare gas remain underutilized, especially in remote and challenging areas like Papua, Indonesia. This research investigates the utilization of such limited gas resources through technical and economic evaluations. This region is characterized by logistical challenges and a scarcity of natural gas users, making it a representative example for similar cases across Indonesia. The study assessed product and technology options for utilizing feed gas with an average volume of 2.5 MMSCFD over a 15-year production lifetime. The findings indicate that converting the gas into CNG and LPG is the most viable solution, yielding an average of 1,264 MMBTU/day of CNG and 4 MT/day of LPG. Economic analysis shows a net present value (NPV) of USD 1.83 million, an internal rate of return (IRR) of 13.01%, and a payback period (POT) of 6.31 years. The use of skid-mounted transportation modules and barges aligns well with the geographical complexities of Eastern Indonesia, offering a scalable and commercially viable approach to stranded gas utilization. This research highlights a sustainable pathway for monetizing marginal gas fields.